AVALIAÇÃO DO EFEITO DA Β (1→6) D-GLUCANA PRODUZIDA PELO FUNGO LASIODIPLODIA THEOBROMAE MMPI SOBRE UM MODELO ANIMAL DE DIABETES - Michel, Renan Garcia (2016)
Diabetes mellitus is a disease with high rate of morbi-mortality, that affects millions of people in the whole world, triggering several healthy complications, social and economic repercussions, due to the greatest propensity that diabetic patients have for developing chronic complications, such as heart diseases, nephropathies, neuropathies and retinopathies. In this context, different researches may assist in the search for new alternatives of treatment to improve diabetic patients’ life quality. In the present study a β (1→6) D-Glucan produced by Lasiodiplodia theobromae (MMPI) was utilized to treat diabetes and its symptoms. β-glucans already have well known biological activities, among them, a hypoglycemic one, attributed to β (1→3) D-Glucan, in addition, glucans with β (1→6) bonding are little studied. 30 adult Wistar rats were treated during 28 days. The animals were divided in 5 groups: SC – Saline Control (treated with saline solution); DS – Diabetic Saline (diabetic-induced and treated with saline solution); PC – Positive Control (diabetic-induced treated with metformin); G5 – 5mg of Glucan (diabetic-induced and treated with β(1→6) D-Glucan 5mg/kg of body weight) and G15 - 15mg of Glucan (diabetic-induced and treated with β(1→6) D-Glucan 15mg/kg of body weight). Alloxan was administrated in a concentration of 150 mg/kg of body weight to induce experimental diabetes in the animals. Body weight and fasting capillary blood glucose were weekly analyzed, and OGTT was performed in the 14º day of treatment. In the end of the 28 days’ treatment, euthanasia was made in order to collect biological material to biochemical analyses and quantification of TBARS in renal and hepatic tissues. There was statistical difference (P<0.05) in body weight evolution, capillary blood glucose and oral glucose tolerance test. A decrease of fasting hyperglycemia and also after the administration of glucose was demonstrated, as well as a better body weight evolution of the rats from group G5 and G15 when compared to the DS group. In biochemical parameters, no statistical difference was demonstrated to creatinine and AST (P>0,05). Moreover, there was an enhancement of ALT and urea levels in all diabetic groups. In hepatic biomarkers, there was a rise of total proteins and albumin to DS and G15 groups, respectively (P<0,05). No difference between groups was noticed in liver TBARS dosage (P>0,05), but there was an increase in kidney’s TBARS to all diabetic groups, with a reduction in the values of the groups treated with the glucan (P<0,05). The treatment with β(1→6) D-Glucan was effective in body weight loss control, and reveled a hypoglycemic effect at fasting, allied to an improvement in glucose response. Thus, it was possible to observe an enhancement in total proteins levels and hypoglycemic effect, beyond a discreet protector effect over lipid peroxidation in kidneys.